2013
DOI: 10.1002/pst.1556
|View full text |Cite
|
Sign up to set email alerts
|

Shift in re‐randomization distribution with conditional randomization test

Abstract: Proschan, Brittain, and Kammerman made a very interesting observation that for some examples of the unequal allocation minimization, the mean of the unconditional randomization distribution is shifted away from 0. Kuznetsova and Tymofyeyev linked this phenomenon to the variations in the allocation ratio from allocation to allocation in the examples considered in the paper by Proschan et al. and advocated the use of unequal allocation procedures that preserve the allocation ratio at every step. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…For the latter, Proshcan et al [22] discovered that with two treatment arms and an unequal allocation ratio, the null distribution of the test statistic may be not centered at zero, which can lead to power loss compared with the population-based test. Similar discoveries were noted by Kuznetsova and Tymofyeyev [17], when the allocation ratio is equal but the randomization test is conditional. Kuznetsova and Tymofyeyev [16] further found that the shift from zero can be mitigated for large sample sizes if, at each step of allocation, a randomization procedure is able to keep the mean ratio the same as the target ratio.…”
Section: Discussionsupporting
confidence: 79%
“…For the latter, Proshcan et al [22] discovered that with two treatment arms and an unequal allocation ratio, the null distribution of the test statistic may be not centered at zero, which can lead to power loss compared with the population-based test. Similar discoveries were noted by Kuznetsova and Tymofyeyev [17], when the allocation ratio is equal but the randomization test is conditional. Kuznetsova and Tymofyeyev [16] further found that the shift from zero can be mitigated for large sample sizes if, at each step of allocation, a randomization procedure is able to keep the mean ratio the same as the target ratio.…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly, it is subject to a serious loss of power compared to normal theory under a population model. Kuznetsova and Tymofyeyev find that such shift even exists in equal allocation when a conditional randomization test is applied. Kuznetsova and Tymofyeyev explain that a shift occurs when a randomization method does not preserve the expected allocation ratio at every step, where the expectation is taken with respect to the distribution of the randomization sequences.…”
Section: Inference Following Covariate‐adaptive Randomizationmentioning
confidence: 99%
“…In this case, the shift in randomization distribution converges to 0 as the sample size increases and is typically very small in studies of moderate size. Of note, when a conditional randomization test is used in studies with equal allocation, a small shift in conditional randomization distribution will be observed [8] with many common randomization procedures, including permuted blocks [9], biased coin randomization [10], or a maximal procedure [4].…”
mentioning
confidence: 99%